Crystal structure of 6-(pyridin-3-yl)-1,3,5-triazine-2,4-diamine-sebacic acid (2/1), C13H17N6O2 - Wang Zhi-Yong; Qian Peng-Xin; Yang Xian-Jiong; Zhang Qi-Long; Xu Hong; Huang Ya-Li (Zeitschrift für Kristallographie - New Crystal Structures)
C8H8N6·C5H9O2, monoclinic, I2/a (no. 15), a = 13.2666(17) Å, b = 11.0435(15) Å, c = 19.778(3) Å, β = 92.707(10)°, V = 2894.4(7) Å3, Z = 8, Rgt(F) = 0.0528, wRref(F2) = 0.1511, T = 293(2) K.